1997
DOI: 10.1095/biolreprod56.5.1228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estradiol and Progesterone withdrawal on the Secretion of and the Temporal Correlation between Pulses of Oxytocin and Prostaglandin F2α, in Ewes1

Abstract: The primary objective was to examine the effects of estradiol and the progesterone receptor antagonist onapristone on the pulsatile secretion of prostaglandin F(2alpha) (PGF(2alpha)) and ovarian and pituitary oxytocin. A 2 x 2 factorial arrangement of estradiol and onapristone treatments was administered to groups of 5 ewes after destruction of ovarian follicles on Day 8 of the cycle. Estradiol treatments consisted of the administration of a silicone elastomer implant, either containing or not containing estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…On the other hand, the lower frequency of OT peaks in CAP-treated gilts as compared to saline-treated ones was accompanied with the lower frequency of PGFM surges. Recent studies by Walker et al (1997) have revealed in ewes that pulses of PGF = which were linked to OT secretion ranged from 36% to 53%. These pulses had a longer duration and a higher amplitude than pulses that were not linked.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lower frequency of OT peaks in CAP-treated gilts as compared to saline-treated ones was accompanied with the lower frequency of PGFM surges. Recent studies by Walker et al (1997) have revealed in ewes that pulses of PGF = which were linked to OT secretion ranged from 36% to 53%. These pulses had a longer duration and a higher amplitude than pulses that were not linked.…”
Section: Discussionmentioning
confidence: 99%
“…336). Oxytocin (157,237,377) stimulates synthesis and secretion of PGF 2␣ from the uterus of guinea pigs (200), heifers (197,308), mares (127), sows (186), and ewes (376). It has recently been proposed that release of luteal PGF 2␣ amplifies the luteolytic signal in an autocrine or paracrine manner (263,369,370).…”
Section: Luteolysismentioning
confidence: 99%